RATIONALE FOR LINGUISTIC PROFILE OF AVIATION ENGLISH LANGUAGE TRAINING COURSE - Petrashchuk, Olena; Vasiukovych, Oksana (Proceedings of National Aviation University (archive), 2015)
The article deals with a new look at learning Aviation English to effectively conduct ‘from air-to-ground’ communication. The communication is based on both radiotelephony phraseology and plain English. The results of aviation oral discourse analysis linguistic profile research are presented in the article. The ratio of phraseology and plain English use identifies the twofold nature of the communication which should be taken into account while developing an English language training course for aviation personnel according to ICAO language requirements.